Aspects of restitution in cases of sexual violence against children: a review of criminal law and its impact on victims - Sinaga, Hasudungan (Universitas Wiralodra, 2023)
This article investigates aspects of restitution in cases of sexual violence against children, focusing on criminal law review and its impact on victims. Sexual violence against children is a severe problem that requires careful legal and judicial attention. One aspect often overlooked is the issue of restitution, which is an effort to compensate for the losses suffered by victims. This research aims to identify issues related to restitution in cases of sexual violence against children and analyze the impact on victims. This study uses a criminal law approach and analyzes various legal provisions relating to restitution in the context of sexual violence against children. We also reviewed previous research on this issue and interviewed legal experts experienced in handling cases of sexual violence against children. The research results show that restitution is often ignored in the judicial process and does not receive the attention it deserves. Victims of sexual violence against children often experience severe physical, emotional, and psychological harm. Therefore, it is essential to consider the role of restitution in helping victims recover and obtain fair compensation for their losses. This study also discusses several challenges in implementing restitution in cases of sexual violence against children and provides recommendations to improve the protection and recovery of victims.